Two-year outcome of MCI subtypes and aetiologies in the Göteborg MCI study. Issue 5 (3rd December 2009) - Nordlund, Arto; Rolstad, Sindre; Klang, Ola; Edman, Åke; Hansen, Stefan; Wallin, Anders
Abstract : Objective: The objective was to study the 2-year outcome of subjects diagnosed as having mild cognitive impairment (MCI). Methods: Two hundred and nine subjects diagnosed as having MCI were examined with a comprehensive neuropsychological test battery and followed up after 2 years. Results: After 2 years, 34 subjects (16%) were lost for follow-up. Those subjects did not differ significantly in terms of MCI subclassification, MMSE score or age and education. Of the 175 subjects followed up, eight (4.5%) had improved to normal, two with amnestic MCI, one from multiple domains MCI, three with single domain MCI and two without any significant impairment at baseline. Forty-four subjects (25%) had progressed to dementia. Of these, 35 were from the multidomain amnestic group and nine from the multidomain non-amnestic group. The combination of Alzheimer-typical biomarkers (total-τ and amyloid beta) and multidomain amnestic MCI was the strongest predictor of progression to Alzheimer's disease, while vascular disease and multidomain amnestic MCI preceded mixed and vascular dementia. Conclusion: The results suggest that memory impairment alone, or impairment in any one cognitive domain alone, is a rather benign condition. Impairment in several cognitive domains is associated with a more severe outcome over 2 years. Also, 20% of the subjects who progressed to dementia, including Alzheimer's disease, did not show memory impairment at baseline, which suggests that memory impairment is not always the first symptom of even the most common dementia disorders.